(Non)respecting of human rights and basic freedoms in context of contemporary social conflicts in Kosovo and Metohia - Aritonović Ivana (Baština, 2011)
In this work an emphasis of problems of (non)respecting human rights and freedoms of ethnical minorities in Kosovo and Metohia, primarily from descriptive and then critic points of view. Foundation for writing this work was a book written by Srđan Slović, Human Rights, CSCE/OSCE and Kosovo Crisis, in which the author theoretically analyzed the concept of human rights and freedoms, as well as difficulties related to respecting those rights within the mission of OSCE in Kosovo and Metohia. It turns out that, after twelve years of Mission's presence, there are still some flagrant violations of human rights and freedoms of ethnic minorities in the province, that are furthermore jeopardized by unilateral declaration of independence of the province and by work of international organizations, such as EULEX, ICO and KFOR that assist on a daily basis so-called Kosovo institutions in tendencies to integrate Serbs into institutional system they do not want to accept. Hence OSCE comes to scene as the only international organization with 'status neutral', to whose representatives Serbs in Kosovo can address and ask for help in cases when their rights are violated.